Analisis Nilai Keadilan Sosial dalam Cerita Rakyat Simeulue dntuk Penguatan Ideologi Pancasila dalam Pembelajaran Bahasa Indonesia - Harunnun Rasyid; Siti Hidaya; Nurliza, Eli; Faisal; Junaidi; Nurul Azmi (Jurnal Serambi Ilmu, 2026)
This study aims to analyze the values of social justice contained in Simeulue folklore and their relevance in strengthening the ideology of Pancasila in Indonesian language learning. The value of social justice is one of the implementations of the fifth principle of Pancasila that is important to instill in students through local culture-based learning. This study employed a qualitative approach with a descriptive method. The research data were obtained from several Simeulue folktales containing representations of social justice values. Data collection techniques were carried out through documentation study and note-taking techniques, while data analysis used content analysis techniques. The results of the study indicate that the values of social justice in Simeulue folklore are reflected through fair attitudes toward others, social concern, mutual cooperation, respect for community rights, and the balanced distribution of rights and obligations in social life. These values have strong relevance to strengthening the ideology of Pancasila, especially the fifth principle, namely Social Justice for All Indonesian People. In addition, the integration of Simeulue folklore into Indonesian language learning can serve as an effective medium for character education in fostering students’ social attitudes, empathy, and awareness of the importance of justice in everyday life. Therefore, Simeulue folklore not only functions as a regional cultural heritage but also as an educational medium in supporting the strengthening of Pancasila ideology in educational environments.